An Analysis of the Prospects of the Use of Magnetic Water Treatment in Foundry Engineering - Dan, Leonid; Trofimova, Larysa (Journal of Casting & Materials Engineering, 2023)
Scientists are currently focused on creating technologies that produce positive results without affecting the environment. One such technology is magnetic water treatment. In this paper, an analytical review of publications devoted to the application of magnetic treatment of water in various branches of engineering, agriculture, and medicine is carried out. Current views on the structure of water molecules, as well as the theories explaining the influence of the magnetic treatment of water on its properties, are reviewed. The results of studies of the influence of water treated by a magnetic field on the properties of molding sand are analyzed, including those in which the authors of the article took part. It is shown that the magnetic treatment of still water can increase the green strength of the molding sand containing this water from 0.035 to 0.052 MPa, and that of water in motion to 0.075 MPa. Thanks to this, the amount of binder in the molding sand can be reduced. It is concluded that the use of magnetically treated water in foundries is promising.